Open property regimes. Issue 2 (September 2016) - Moritz, Mark
In the literature on the commons, open access is considered the absence of a property regime and equated with a tragedy of the commons. However, a longitudinal study of mobile pastoralists in the Far North Region of Cameroon shows that open access is not the absence of rules and does not lead to a tragedy of the commons. Current theoretical models cannot explain this phenomenon of management of common-pool grazing resources in a situation of open access. Here I propose a new property regime – an open property regime – that solves this paradox. First, I will explain how open property regimes function as complex adaptive systems using our study of mobile pastoralists in Cameroon. Second, I will describe four other cases of pastoral systems with similar open property regimes. Finally, I discuss the key characteristics that these pastoral systems have in common and outline a new theoretical model of open property regimes.